Cultural and Aesthetic Concerns that Shape Recaizade Mahmut Ekrem's Translation of Atala - Arslan, Nihayet (AHMET YESEVI UNIV, 2017)
As the Tanzimat period is the first major milestone in Turkish cultural history with regard to transition to Western civilization, the characteristics of the literary works that were translated in that period, why they were preferred and how they were translated are important for our literary and cultural history as well as translation studies. The French writer, Chateaubriand's novel titled Atala, which is the topic of this article, was first translated into Ottoman Turkish by Recaizade Mahmut Ekrem in 1872. Investigating how Atala, which is a pioneering work dealing with the most significant themes of Romantic movement such as love, exoticism and religion, is worthwhile as it provides an example of translator's attitude in the first translations. It also brings light to the reasons behind the cultural and aesthetic concerns that define the translator's attitude. Recaizade Mahmut Ekrem was raised in the Ottoman culture and he got familiar with the Western culture and literature through his mastery of French language. It is therefore expected that he would have some cultural concerns while translating Atala - a work that he much appreciated - into Ottoman Turkish, especially given the period he lived in. In the present study, such concerns that lead the translator to give priority to the target language will be identified and the study will focus on these points.
Keywords: First translations; Recaizade Mahmut Ekrem; Atala; target culture; Tanzimat period; romanticism; Area Studies